Placement of Tissue Marker and Wire Localization Before Conservative Breast Surgery of Invasive Ductal Carcinoma of Breast (Bangladesh Journal of Radiology and Imaging, 2026)
Radiologist use marker clips as tissue marker before starting neoadjuvant chemotherapy to place in the cancer site to see the response, later in mammographic image this marker helps identify cancer disappear largely or not. It is also to help prevent taking repeated biopsy sample from same site. If mammo shows normal appearance but ultrasonogram shows abnormality, then a marker need to place during ultrasonogram and re mammogram is done to locate the lesion. Most lumps can be felt but sometimes we cannot actually feel anything but changes in breast may be found in mammogram or ultrasonogram. So it needs a wire localization and a marker to guide us to the area for surgery.This is done either by using a skin marker under USG guidance or by placing a wire into the abnormality either by mammogram or ultrasonogram guidance.BJRI, 2024; VOL. 32(2): 145-152